Does the quantity of scientific publications reflect the quality? A rising issue for promotion in developing countries - (:unkn) unknown (My University, 2000)
Objective: Turkey's international scientific ranking increased from 42nd in 1991 to 25th place in 1998. In this study, we intended to clarify Marmara University School of Medicine's scientific publication trend for the last four years between 1995-1998 in comparison with previous four-year period between 1991-1994, regarding quality. Methods: We sorted out the total number of publications from all academic institutions in Turkey, Marmara University and Marmara University School of Medicine indexed in Science Citation Index between 1991 and 1998. We compared the total number of faculty members and 'scientific publication per faculty member (ppf)' on a yearly basis in order to place their trend especially by comparing the time period of the first four years between 1991 and 1994 to the last four years. Results: The total number of publications from the school of medicine increased from 15 in 1991 to 80 in 1998. The percentage of publications from the school of medicine out of all university publications was determined to be 63% in 1991, 77% in 1994 and 58% in 1998. ppf in school of medicine was 0.07 in 1991, 0.15 in 1994 and 0.22 in 1998. Although the number of articles increased from 11 in 1991 to 44 in 1998, its percentage within total publications decreased from 78% in 1991 to 55% in 1998. Conclusion: Although the number of the publications from the school of medicine increased, its percentage among all publications in the university has decreased. In addition to this, most authors preferred to publish papers other than articles which in turn resulted a decline in quality of published material. Therefore, the total number of publications from the medical faculty does not reflect an accurate interpretation of its current scientific situation in Marmara University.
Keywords: Marmara University; Publication; School of medicine; Science citation index; Scientific rank